A conserved sequence motif in 3′ untranslated regions of ribosomal protein mRNAs in nematodes - Hajarnavis, Ashwin (Cold Spring Harbor Laboratory Press, 2006)
The 3′ untranslated regions (3′ UTR) of eukaryotic genes can contain motifs involved in regulation of gene expression or localization at the post-transcriptional level. This study concerns the identification of novel, conserved elements in 3′ UTRs of many ribosomal protein mRNAs in Caenorhabditis elegans and Caenorhabditis briggsae. Analysis of the region around the polyadenylation signal in many ribosomal protein mRNAs indicates the conservation of a sequence motif UUGUU occurring both before and immediately after the polyadenylation signal. Building a statistical model of this motif and searching a database of C. elegans 3′ UTRs reveals that this motif is also present in the 3′ UTR of some genes involved in translation and ribosome maturation, among others. We suggest that this signal may be involved in translation or other message-level regulation of ribosomal genes in C. elegans.